Monsoon rains and icicle drops - Southwell, Libby (Pier 9, 2006)
Libby Southwell has been to some amazing places and seen some incredible things - she was an advertising executive in Sydney when her beloved fiancee died in an accident. Plunged into grief, she first went to Sri Lanka. Her journeys took her to Nepal, Mongolia and a Buddhist retreat. This volume tells her story.